Interplay Between Plasma Membrane Lipid Alteration, Oxidative Stress and Calcium-Based Mechanism for Extracellular Vesicle Biogenesis From Erythrocytes During Blood Storage - Cloos, Anne-Sophie; Ghodsi, Marine; Stommen, Amaury; Vanderroost, Juliette; Dauguet, Nicolas; Pollet, Hélène; D’Auria, Ludovic; Mignolet, Eric; Larondelle, Yvan; Terrasi, Romano; Muccioli, Giulio G.; Van Der Smissen, Patrick; et al. (Frontiers in Physiology, 2020)
The shedding of extracellular vesicles (EVs) from the red blood cell (RBC) surface is responsible for RBC biconcavity loss and hypo-osmotic fragility. Two main models for EV shedding, respectively based on calcium rise and oxidative stress, have been proposed in the literature but the role of the plasma membrane lipid composition and properties is not understood. Using blood in EDTA/K+ tubes stored for up to 4 weeks at 4°C as a relevant RBC vesiculation model, we showed here that the RBC plasma membrane lipid composition, organization in domains and biophysical properties were progressively modified during storage and contributed to the RBC vesiculation. First, the membrane content in cholesterol and linoleic acid decreased whereas lipid peroxidation and spectrin:membrane occupancy increased, all compatible with higher membrane rigidity. Second, phosphatidylserine surface exposure showed a first rapid rise due to membrane cholesterol decrease, followed by a second calcium-dependent increase. Third, lipid domains mainly enriched in GM1 or sphingomyelin strongly increased from the 1st week while those mainly enriched in cholesterol or ceramide decreased during the 1st and 4th week, respectively. Fourth, the plasmatic acid sphingomyelinase activity considerably increased upon storage following the sphingomyelin-enriched domain rise and potentially inducing the loss of ceramide-enriched domains. Fifth, in support of the shedding of cholesterol- and ceramide-enriched domains from the RBC surface, the number of cholesterol-enriched domains lost and the abundance of EVs released during the 1st week perfectly matched. Moreover, RBC-derived EVs were enriched in ceramide at the 4th week but depleted in sphingomyelin. Then, using EDTA/K+ tubes supplemented with glucose to longer preserve the ATP content, we beter defined the sequence of events. Altogether, we showed that EV shedding from lipid domains only represents part of the global vesiculation mechanistics, for which we propose four successive events (cholesterol domain decrease, oxidative stress, sphingomyelin/sphingomyelinase/ceramide/calcium alteration and phosphatidylserine exposure).